Analisis Pengaruh Strategi Digital Marketing Terhadap Daya Tarik Mahasiswa Baru Di Universitas Islam Kebangsaan Indonesia - Humaira, Novida; Reza, Muhammad; Saputra, Dedi; Hanum, Lutvia (Ekonosfera: Jurnal Ekonomi, Akuntansi, Manajemen, Bisnis dan Teknik Global, 2025)
Increasing the attraction of new students is one of the main challenges for universities in Indonesia, especially in the face of rapid development of digital technology. For this reason, universities need to utilize the right digital marketing strategy to attract the attention of prospective students. This study aims to analyze the effect of digital marketing strategies on attracting new students at Universitas Islam Kebangsaan Indonesia (UNIKI). The method used in this research is a quantitative method with a survey as a data collection instrument. The analysis technique used is linear regression to measure the relationship between digital marketing factors, namely social media, websites, and digital advertising to attract new students. The results showed that digital marketing strategies, especially through social media, have a significant influence on prospective students' decisions to choose UNIKI. Therefore, it is recommended that UNIKI optimize the use of digital platforms in order to introduce study programs and increase interaction with prospective students.